The role of hepatitis B virus genome variations in HBV-related HCC: effects on host signaling pathways - Shoraka, Shahrzad; Hosseinian, Seyed Mahdi; Hasibi, Ayda; Ghaemi, Amir; Mohebbi, Seyed Reza (Frontiers in Microbiology, 2023)
Hepatocellular carcinoma (HCC) is a significant global health issue, with a high prevalence in many regions. There are variations in the etiology of HCC in different regions, but most cases are due to long-term infection with viral hepatitis. Hepatitis B virus (HBV) is responsible for more than 50% of virus-related HCC, which highlights the importance of HBV in pathogenesis of the disease. The development and progression of HBV-related HCC is a complex multistep process that can involve host, viral, and environmental factors. Several studies have suggested that some HBV genome mutations as well as HBV proteins can dysregulate cell signaling pathways involved in the development of HCC. Furthermore, it seems that the pathogenicity, progression of liver diseases, response to treatment and also viral replication are different among HBV mutants. Understanding the relationship between HBV genome variations and host signaling pathway alteration will improve our understanding of the molecular pathogenesis of HBV-related HCC. Furthermore, investigating commonly dysregulated pathways in HBV-related HCC is necessary to discover more specific therapeutic targets and develop more effective strategies for HCC treatment. The objective of this review is to address the role of HBV in the HCC progression and primarily focus on the impacts of HBV genome variations on HCC-related signaling pathways.